RAGE and HMGB1 expressions in fetal membranes of premature rupture of membranes patients (Medical Journal of Indonesia, 2022)
BACKGROUND Premature rupture of membranes (PROM) often occurs in pregnancy. The fetal membrane weakening is caused by inflammation involving receptor activation for advanced glycation end-products (RAGE) and high mobility group box protein 1 (HMGB1). The associations between RAGE and HMGB1 with PROM are rarely studied. Hence, this study aimed to determine those associations in fetal membranes with PROM occurrence. METHODS This case-control study was conducted at Dr. Ramelan Central Naval Hospital, Surabaya, Indonesia, from August to November 2019. The subjects, determined using a non-probability sampling method (a saturated sample), were divided into PROM and normal pregnancy with intact fetal membranes (control) groups. Fetal membrane specimens were collected during vaginal and cesarean section deliveries. The expressions of RAGE and HMGB1 were determined using the immunohistochemical method and further analyzed using the Mann–Whitney U test. RESULTS The expression of RAGE in fetal membranes with PROM was significantly higher than the control (52.74% versus 14.9% expression/mm2, p<0.001), as well as the expression of HMGB1 (45.9% versus 8.5% expression/mm2, p<0.001). CONCLUSIONS The higher expressions of RAGE and HMGB1 in fetal membranes were associated with PROM.